Frequency of Pornography Use and Sexual Health Outcomes in Sweden: Analysis of a National Probability Survey. Issue 10 (12th September 2021) - Malki, Kinda; Rahm, Christoffer; Öberg, Katarina Görts; Ueda, Peter
ABSTRACT: Background: Little is known about pornography use and its relationship with sexual health outcomes in the general population. Aim: To assess frequency of pornography use and the association of sexual health outcomes with frequent pornography use in Sweden. Methods: Cross-sectional analysis of 14, 135 participants (6, 169 men and 7, 966 women) aged 16–84 years in a Swedish nationally representative survey from 2017. We used logistic regression to assess the association of sexual health outcomes with use of pornography ≥3 times/wk. Outcomes: Frequency of pornography use (never; less than once/mo to 3 times/mo; 1–2 times/wk; 3–5 times/wk; and daily or almost daily) and sexual health outcomes (eg, sexual satisfaction and sexual health problems). RESULTS: In total, 68.7% of men and 27.0% of women used pornography. Among men aged 16–24 years, 17.2% used pornography daily or almost daily, 24.7% used pornography 3–5 d/wk and 23.7% used pornography 1–2 d/wk. Among women aged 16–24 years, the proportions were 1.2% for daily or almost daily, 3.1% for 3–5 times/wk, and 8.6% for 1–2 times/wk. Frequency of pornography use decreased with age among both men and women. While 22.6% of all men and 15.4% of all women reported that their or a sex partner's pornography use predominantly had positive effects on their sex life, 4.7% of men and 4.0% of women reported that the effects were predominantly negative. Variables indicating sexual dissatisfaction and sexual health problems were associated with use of pornography ≥3 times/wk: for example, dissatisfaction with sex life (age-adjusted odds ratio [aOR]: men 2.90 [95% CI 2.40–3.51]; women 1.85 [95% CI 1.09–3.16]), not having sex in the preferred way (aOR: men 2.48 [95% CI 1.92–3.20]; women 3.59 [95% CI 2.00–6.42]) and erection problems (aOR: men 2.18 [95% CI 1.73–2.76]). Clinical Implications: While frequent pornography use is common, potential effects on sexual health outcomes are likely to differ between individuals. Strength & Limitations: We used a large and recent nationally representative survey with detailed information regarding frequency of pornography use. The temporality of associations of sexual health variables with frequency of pornography use could not be assessed. CONCLUSION: In this analysis of a nationally representative survey in Sweden, we found that frequent pornography use was common among young men; that reporting predominantly positive effects of pornography use on the sex life was more common than reporting predominantly negative effects; and that sexual dissatisfaction and sexual health problems were associated with using pornography ≥3 times/wk.